(untitled) (Vietnam Journal of Community Medicine, 2022)
Evaluate the effective treatment of chills after spinal anesthesia with magnesium sulfate for pregnant women undergoing cesarean section and evaluate side effects of the above treatment method. A cross-sectional descriptive study of 145 women receiving spinal anesthesia for cesarean section, age ranges from 18-50 years old, ASA I-II at the Anesthesia and Reanimation Department of Nghe An Obstetrics and Children’s Hospital during January 2021 to october 2021. The time to achieve the treatment effect after 10 minutes, 20 minutes accounted for the highest rate of 28.28% and 31.03%. Very satisfaction: 72.41% satisfied; 20.69% satisfied. The most common undesirable effects: hot flushes: 37.93%; nausea and vomiting 8.28%.